Helicoverpa armigera herbivory negatively impacts Aphis gossypii populations via inducible metabolic changes. Issue 6 (24th March 2022) - Zheng, Shuaichao; Liu, Weijiao; Luo, Junyu; Wang, Lisha; Zhu, Xiangzhen; Gao, Xueke; Hua, Hongxia; Cui, Jinjie
Abstract: BACKGROUND: Helicoverpa armigera and Aphis gossypii are two important insect species that feed on cotton plants. These insects have distinct abilities to induce plant resistance and tolerate plant toxins, which results in interspecific competition imbalance that may be fatal to the low‐tolerance A. gossypii and force these insects to develop avoidance behaviors and subsequently separate from their niche. We implemented ecological experiments to test the effects of H. armigera ‐induced plant resistance and behavioral avoidance in A. gossypii, and employed transcriptomics and metabolomics analyses to reveal changes in resistance genes and metabolites in plants. RESULTS: Our results demonstrate that cotton plants induced by H. armigera cause significant inhibitory and avoidance effects on A. gossypii insect populations. Electrical penetration graph (EPG) analysis showed changes in plant resistance induced by H. armigera leading to a decreased feeding efficiency of A. gossypii . In addition, genes associated with jasmonic acid and ethylene signaling pathways were significantly up‐regulated in cotton plants after H. armigera induction, which led to a significant up‐regulation of metabolites inducing plant resistance. These observations were corroborated by bioactivity analysis on metabolites, which showed that jasmonic acid, gossypol and tannins have significant inhibitory effects on A. gossypii populations. In contrast, methylparaben is associated with avoidance behaviors on A. gossypii populations. CONCLUSION: Our study suggests that the differences in the ability to induce plant resistance and tolerance between two non‐predatory insects were lethal to low‐tolerance A. gossypii insects, which might be a major factor determining their niche differentiation. This was further demonstrated by screening anti‐insect and bio‐hormonal metabolites. Our study provides a reference for investigating the evolutionary relationship between non‐predatory insects and insights to implement effective insect biocontrol. © 2022 Society of Chemical Industry Abstract : We revealed that plant resistance response induced by the H. armigera had a repellent effect on A. gossypii populations. Finally, two kinds of insects produced differentiation in living space. Our results also provided references for resistance breeding and the development and utilization of biological pesticides.